PREPARING STUDENTS TO BECOME RESPONSIBLE CITIZENS - Diyantari Diyantari; Irawaty Irawaty (Jurnal Ilmiah Mimbar Demokrasi, 2017)
Character building is one of the most important issues in education. The Government of Indonesia states clearly the issue of preparing responsible citizens in the regulations of its national education system. This research aims at investigating what teachers should do in classroom in order to prepare students to become responsible citizens. It is a qualitative research in which the data is gathered through library research. It can be concluded that teachers should develop democratic classroom rules and clear expectations, share responsibility, set clear goals and plans, take aproblem-solving approach, encourage students to care for others, encourage students to compete with themselves to achieve their personal best, involve students in community activities, and keep a journal to evaluate in order to prepare students to become responsible citizens through well prepared classroom management.